Heterogeneous MIL-88A on MIL-88B hybrid: A promising eco-friendly hybrid from green synthesis to dual application (Adsorption and photocatalysis) in tetracycline and dyes removal - Rabeie, Bahareh; Mahmoodi, Niyaz Mohammad (Journal of colloid and interface science, 2024)
[Display omitted] •Green synthesis of heterogeneous core-shell MIL88B@MIL88A composites.•Dual functional materials as environmentally friendly photocatalysts and adsorbents.•Heterogeneous MIL-88B@MIL-88A (Core: rod-like MIL-88B and shell: MIL-88A).•Catalytic degradation and adsorption of Tetracycline and dyes. Herein, the green synthesis of heterogeneous dual functional MIL88A-on-MIL88B hybrids (MIL: Materials InstituteLavoisier) with different amounts of MIL88B compared to MIL88A, including 1:2, 1:1, and 2:1, has been carried out. The photocatalytic degradation of tetracycline and adsorption of tetracycline and dyes (Direct Red 80, Direct Red 23, Acid Blue 92, and Reactive Orange 14) were investigated. Although the ratio of MIL88A-on-MIL88B (1:1) hybrid displayed the best activity, there is a slight difference in the photocatalytic performance of the other mass ratios studied. The result revealed that after 70 min of forming MIL88A on MIL88B, the best pollutant removal performance is obtained. During the limited synthesis time, the lopsided growth of MIL88A on the MIL88B surface limits the formation of sufficient functional groups and new pores between MIL88B as the substrate and MIL88A, which are effective and decisive in the performance. In the photocatalytic studies, the synthesized composite had good compatibility with the zero-order kinetics, and hydroxyl radicals were recognized as the most active species in the photocatalytic reaction. In the adsorption process, the MIL88A-on-MIL88A composite followed pseudo-second-order kinetics and the Langmuir isotherm. Besides, mechanisms such as π-π interaction/stacking, hydrogen bonding, and π-metal interaction were proposed for the pollutant adsorption process.